Influences of Environmental Conditions to Phytoconstituents in Clitoria ternatea (Butterfly Pea Flower) – A Review - Jamil, Nadzirah; Mohd Zairi, Mohd Naqiuddin; Mohd Nasim, Nur A'in; Pa'ee, Furzani (Journal of Science and Technology, 2018)
: Extreme environmental conditions will consequently become a disturbance on all phases of plant growth. Malaysia is one of the developing countries that face challenges of extreme environmental conditions from climate change such as water availability and soil salinity. In response to global climate change, plants are trying to survive through several adaptation mechanisms. Clitoria ternatea or also known as Butterfly pea flower is a potential plant that can tolerate different environmental parameters. Besides, C. ternatea contains essential phytochemical compounds for pharmaceuticals, textile, medicinal and food industries. C. ternatea is originated from tropical Asia countries and it is widely available in the Asian region. Butterfly pea flower has attractive petal colours due to the presence of its bioactive compounds. C. ternatea is claimed as curing various ailments and has great antioxidant activity due to their bioactive compounds such as anthocyanins, alkaloid, steroid, tannin, reducing sugars and flavonoid. Clitoria ternatea has been evaluated as a potential medicinal plant, such as antiviral, anti-inflammatory, anti-allergic and prevent from cardiovascular damage. Meanwhile, by varying different environmental parameters, the adaptations of phytochemical in C. ternatea is expressed variously. Hence, this paper reviews the physiological effect of growth conditions on Clitoria ternatea and its effect on the production of beneficial phytoconstituents.